Conjugated Polyelectrolyte‐Induced Self‐Assembly of Alkynylplatinum(II) 2, 6‐Bis(benzimidazol‐2′‐yl)pyridine Complexes. Issue 46 (2nd October 2015) - Chan, Kevin; Chung, Clive Yik‐Sham; Yam, Vivian Wing‐Wah
Abstract: Water‐soluble cationic alkynylplatinum(II) 2, 6‐bis(benzimidazol‐2′‐yl)pyridine (bzimpy) complexes have been demonstrated to undergo supramolecular assembly with anionic polyelectrolytes in aqueous buffer solution. Metal–metal‐to‐ligand charge transfer (MMLCT) absorptions and triplet MMLCT ( 3 MMLCT) emissions have been found in UV/Vis absorption and emission spectra of the electrostatic assembly of the complexes with non‐conjugated polyelectrolytes, driven by Pt⋅⋅⋅Pt and π–π interactions among the complex molecules. Interestingly, the two‐component ensemble formed by [Pt(bzimpy‐Et)CCC6 H4 (CH2 NMe3 ‐4)]Cl2 (1 ) with para ‐linked conjugated polyelectrolyte (CPE), PPE‐SO3 −, shows significantly different photophysical properties from that of the ensemble formed by 1 with meta ‐linked CPE, m PPE‐Ala. The helical conformation of m PPE‐Ala allows the formation of strong m PPE‐Ala–1 aggregates with Pt⋅⋅⋅Pt, electrostatic, and π–π interactions, as revealed by the large Stern–Volmer constant at low concentrations of 1 . Together with the reasonably large Förster radius, large HOMO–LUMO gap and high triplet state energy of m PPE‐Ala to minimize both photo‐induced charge transfer (PCT) and Dexter triplet energy back‐transfer (TEBT) quenching of the emission of 1, efficient Förster resonance energy transfer (FRET) from m PPE‐Ala to aggregated 1 molecules and strong 3 MMLCT emission have been found, while the less strong PPE‐SO3 − –1 aggregates and probably more efficient PCT and Dexter TEBT quenching would account for the lack of 3 MMLCT emission in the PPE‐SO3 − –1 ensemble. Abstract : FRET architectonics : Supramolecular assemblies formed by alkynylplatinum(II) 2, 6‐bis(benzimidazol‐2′‐yl)pyridine complexes and conjugated polyelectrolytes of different electronic properties and conformations have been found to be stabilized by Pt⋅⋅⋅Pt and π–π interactions. Such ensembles exhibit different photophysical properties and excited state chemistry, which have been rationalized by the differences in Förster resonance energy transfer (FRET) efficiency, extent of polymer–metal complex aggregate formation, photo‐induced charge transfer (PCT), and Dexter triplet energy back‐transfer (TEBT) quenching.